Esquerdas do mundo, uni-vos! - da Costa Ribeiro, Pedro Mollica (Revista Direito e Práxis, 2018)
DOI:10.1590/2179-8966/2018/34226 RESENHA Esquerdas do mundo, uni-vos! Boaventura de Souza Santos.São Paulo: Boitempo, 2018, 87 p. Pedro Mollica da Costa Ribeiro Universidade do Estado do Rio de Janeiro, Rio de Janeiro, Brasil. E-mail: pedromcostaribeiro@gmail.com ORCID: https://orcid.org/0000-0003-0881-8299.